THE SPIRITUAL STRUCTURE OF “INNATE WHOLENESS” OF THE HERO MANAS: FORMATION OF PERSONAL QUALITIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The epic Manas is one of the most significant cultural heritages of the Kyrgyz people. The image of the hero Manas embodies not only military skill and political wisdom but also a deep and stable spiritual structure. The concept of “innate wholeness” is considered a philosophical category that emphasizes the inner integrity of the subject and natural spiritual maturity. Its theoretical foundations can be found in Eastern philosophy, particularly in Buddhist teachings on the nature of consciousness.This article examines the formation of Manas’s personality, his sense of mission, and his attitude toward conflicts through the concept of “innate wholeness,” using methods of textual analysis and theoretical research. The study systematically analyzes how the hero maintains spiritual stability and value integrity in conditions of chaos and continuous crises.The results show that the heroism of Manas is grounded not only in external achievements but also in inner maturity, self-awareness, and a stable spiritual structure. These qualities constitute one of the key factors that have made him a spiritual symbol of the Kyrgyz people.
Keywords: Manas, heroic epic, innate wholeness, national spirit, subject consciousness, symbol, wisdom